Offensive and Defensive Competitive Marketing Strategy: The Development of Construct & Measurements - Heriyati, Pantri; Heruwasto, Ign; Wahyuni, Sari (UI Scholars Hub, 2021)
Malaysia is opening parts of its services to greater foreign participation due to globalisation. Local banks have since consolidated a decade ago and foreign banks expanding their businesses in local markets have intensified the competition. As a result, credit card adoption is getting more challenging to marketers. Hence effective marketing strategies are important. The theoretical model of the paper is based on the buyer behaviour model by Kotler and Armstrong (1999). The model identifies the major factors which influence consumer buyer behaviour and how buyer decision process affects the buyer behaviour. The paper aims to examine the effectiveness of marketing strategies in enhancing credit card adoption. A survey was conducted on 251 respondents using a survey instrument. The data collected was analyzed using a series of statistical techniques. The results of the analysis are discussed and the findings revealed that social status is an important factor associated with customers’ behaviour. This factor is also associated with sales promotions. Findings also revealed that credits cards that create social admiration are preferred